Putting Learning into Practice: Integrating Social Media, Crowd Learning, and #ColinKaepernick in an Introductory African American History Class - Boyce, Travis (Radical Teacher, 2017)
African American history is indeed a dynamic discipline that can be used as a framework to understand the present lives of African Americans as well as the broader American society. As a university professor who values social media as a useful tool in the traditional classroom, I am most interested in using it in my introductory African American history course to make history relevant to my students, especially since a social media post accompanied with a popular hash tag has the ability go viral and reach a wider audience than a traditional academic paper. Many instructors are looking for opportunities to engage students in social and intellectual discourse about history. This article will deconstruct social media posts associated with the hash tag Colin Kaepernick or the like as a teaching strategy to help students enrolled in an introductory African American history course. The idea is to put their learning into practice by encouraging them to actively engage with others on topics relevant to the course content. This article will demonstrate that although the discourse surrounding Kaepernick is polarizing, it is an excellent pedagogical strategy to help students put their learning into practice and engage with a wider audience on topics discussed in an introductory African American history course.